Animal babies on mountains - Schofield, Jennifer (Kingfisher Publications London, 2005)
Woof! Woof! Look at my shiny black nose, Who is my mummy? Beautiful, heart-warming photographs of animal babies with their parents in their natural habitat. 1-4 yrs